Enhanced performances of triboelectric nanogenerators by filling hierarchical flower-like TiO2 particles into polymethyl methacrylate film. Issue 26 (30th June 2020) - Jian, Gang; Meng, Qingzhen; Jiao, Yong; Meng, Fang; Cao, Yanpeng; Wu, Mingfang
Abstract : In this study, a flower-like TiO2 filled polymethyl methacrylate (PMMA) composite is presented as a positive tribo-material to produce an excellent-performance triboelectric nanogenerator (TENG). Abstract : In this study, a flower-like TiO2 filled polymethyl methacrylate (PMMA) composite is presented as a positive tribo-material to produce an excellent-performance triboelectric nanogenerator (TENG). By working in conjunction with polydimethylsiloxane (PDMS), the flat-surface PDMS/PMMA-flower TiO2 TENG generates a voltage of 1200 V, a current of 139 mA m −2 and an output power of 34.85 W m −2, showing significant enhancement compared with its counterpart utilizing neat PMMA as the positive tribo-material under the same operating conditions, whose voltage is 620 V, current is 78 mA m −2 and output power is 13.89 W m −2, respectively. The performance of the TENG is highly dependent on filler loadings of TiO2 flower particles in PMMA composites with an optimal filler loading of 40 wt% with the highest performances. The flower TiO2 is vital to the enhanced performances of the TENG, which is due to the modified surface, the tailored dielectric constant and the space charge polarization. The TENG is capable of powering 600 light emitting diodes, a calculator and a digit display, and applied in self-powered electrophoretic deposition of oxide films. This work demonstrates a facile, low-cost approach for obtaining high-performance TENGs utilizing a PMMA-flower TiO2 composite as the positive tribo-material for applications in sustainable power systems.